Determinan Penerimaan Daerah dari Sektor Pariwisata di Kabupaten/Kota Provinsi Jambi - Qorina Novitri; Junaidi Junaidi; Muhammad Safri (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
The purpose of this study was to analyze whether the number of hotel room occupancy rate, the GDP of the tourism sector, the number of restaurants and eating houses, the average length of stay, and number of tourists influence the reception area of the tourism sector in the District / City of Jambi Province. The analysis used in this study is the analysis of growth, econometric analysis using panel data models, and analysis of barriers and opportunities. The results showed that simultaneous number of hotel room occupancy rate, the GDP of the tourism sector, the number of restaurants and eating houses, the average length of stay, and number of travelers significant effect on local revenues from the tourism sector in the District / City of Jambi Province. Keywords: Regional Revenues from the tourism sector, Total Room Occupancy Rate, GDP Tourism Sector, Total Restaurant and Eating, Average Length of Stay